Follow-up of the academic trajectory of the cohort enrolled in a public university in Colombia, 2011: dropout, lag and graduation (Revista Electrónica Calidad en la Educación Superior, 2024)
Historical cohort study that describes the academic trajectory associated with dropout, lag and graduation in undergraduate programs at a public university in Colombia. A sample of 3120 people enrolled in 2011 in study plans of ten academic periods was analyzed, who were followed up to four semesters after the duration of the program. Students with up to four disengagement episodes were found, 61.6% of whom disengaged at least once. Attrition, graduation and lagged students were 52.7%, 38.4% and 8.9%, respectively. This type of descriptive analysis can be used to determine operational criteria for monitoring student dropout.
Keywords: school failure; higher education; university student; dropout